Communal sheep farmer’s knowledge and attitudes on the incidence of gastrointestinal parasites in the Eastern Cape, South Africa - Jansen, Mlungisi Selby; Nyangiwe, Nkululeko; Diniso, Yanga Simamkele; Yawa, Mandla; Mpendulo, Thando Conference; Dastile, Mzwethu; Jaja, Ishmael Festus (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Gastrointestinal parasites (GIPs) negatively impact small ruminant production and productivity nationwide, particularly in tropical and sub-tropic regions. Amongst other nematodes, Haemonchus contortus, Trichostrongylus colubriformis, and Teladorsagia circumcincta are the most common species in small ruminants’ animals. Thus, this study aimed to investigate communal sheep farmer’s knowledge and attitudes toward GIPs in the Eastern Cape Province, South Africa. Materials and Methods: A cross-sectional survey was conducted between September and November 2018 from three agro-ecological zones, namely, arid region, semi-humid, and humid. All data from this study were analysed with the Statistical Analysis System. Results: Of the total of 107 farmers who participated in the study, 69% were males, and 38% were females. Most livestock owners (85%) were aged >46 years old across all the study areas. The majority of farmers (83%) perceived that their animals are susceptible to wireworm (H. contortus) during the hot-wet season, followed by the hot-dry season (14%), with relatively low during the cold season (2%). Most farmers (85%) interviewed revealed that lambs are more exposed to parasitic infection, than mature sheep (15%) across all agro-ecological zones. An insignificant number of farmers (8%) with knowledge about GIPs life cycle and its biology (92%) across all agro-ecological zones. This study reveals a significant increase in the occurrence of GIPs over the past few years across all agro-ecological, with largely (67%) attributed to the resistance of the strain to deworming remedies and changes in climatic weather patterns (33%). The farming experience was strongly (p < 0.05) associated with the farmer’s gender and age. Helminths were reported significantly higher (p < 0.05) in humid zones than in other agro-ecological zones. Conclusions: This study concludes that most farmers perceived lambs as more susceptible to GIPs than old sheep. Therefore, farmers should be enlightened about the infection and transmission dynamics of the GIPs to develop appropriate control measures against worm infection to boost sheep production in the study area. It was also suggested that farmers should adhere to remedial instruction and adopt rotational deworming programs to avoid anthelmintic resistance. J. Adv. Vet. Anim. Res., 8(4): 351-358, July 2022 http://doi.org/10.5455/javar.2022.i602